2015
DOI: 10.1038/eye.2015.22
|View full text |Cite
|
Sign up to set email alerts
|

Comparision of surgical outcomes of intraocular lens refixation and intraocular lens exchange with perfluorocarbon liquid and fibrin glue-assisted sutureless scleral fixation

Abstract: Aim The purpose of this study was to compare the surgical outcomes of intraocular lens (IOL) refixation with intraocular lens exchange using perfluorocarbon liquid (PFCL) and fibrin glue-assisted sutureless scleral fixation surgery in patients with dislocation of the IOL. Methods Twenty-five eyes of 25 patients who underwent surgery for dislocated IOLs with PFCL and fibrin glue-assisted scleral fixation were studied; 13 eyes experienced IOL refixation (in-the-bag and out-of-the-bag), and 12 eyes experienced IO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
71
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(77 citation statements)
references
References 34 publications
3
71
0
1
Order By: Relevance
“…20 In two retrospective studies of IOL dislocation surgery, mean SIAs of 0.6 and 0.7 D after IOL repositioning, and 0.7 and 1.1 D after IOL exchange with a corneal incision was found. 11,14 Also other IOL dislocation studies have shown increased astigmatism after exchange surgery. 10,12 Further- Change from preoperative to postoperative visit SE change,# D À0.68 6 1.14 (P ¼ 0.002) (n ¼ 33) þ0.44 6 1.25 (P ¼ 0.09) (n ¼ 25) 0.001 * Mean for patients with information and that attended the 6-month postoperative visit.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…20 In two retrospective studies of IOL dislocation surgery, mean SIAs of 0.6 and 0.7 D after IOL repositioning, and 0.7 and 1.1 D after IOL exchange with a corneal incision was found. 11,14 Also other IOL dislocation studies have shown increased astigmatism after exchange surgery. 10,12 Further- Change from preoperative to postoperative visit SE change,# D À0.68 6 1.14 (P ¼ 0.002) (n ¼ 33) þ0.44 6 1.25 (P ¼ 0.09) (n ¼ 25) 0.001 * Mean for patients with information and that attended the 6-month postoperative visit.…”
Section: Discussionmentioning
confidence: 99%
“…Despite its importance for daily life activities, only a few studies have compared refractive outcomes between different operation methods for late in-the-bag IOL dislocation, 3,[11][12][13][14] and to our knowledge, no previous randomized trial has been conducted. Because a consensus on the surgical technique has not yet been established, nor with regard to refractive outcomes, we considered it of clinical relevance to perform such a comparison.…”
mentioning
confidence: 99%
“… Creation of suture loop around the haptic with surgical maneuvers around the dislocated PCIOL inside the eye – ”Cow-hitch knot” or the “Lasso” technique[ 12 ] Externalization of haptic and fixing it to sclera by the creation of scleral tunnels with or without scleral flaps (scleral tuck). [ 7 8 21 22 23 ] …”
Section: Discussionmentioning
confidence: 99%
“…There are limited studies in literature reporting the management of dislocated IOLs by a sutureless closed globe scleral refixation. [ 7 8 19 20 21 22 23 ] This study analyses the treatment outcomes following scleral refixation of dislocated IOLs using the scleral tuck method and compares the outcomes between the two techniques used.…”
mentioning
confidence: 99%
“…9 IOL explantation and exchange is technically difficult procedure associated with complications like corneal endothelial cell loss, aggravation of refractive error, zonular dehiscence, IOL tilting, and decentration. [10][11][12]…”
Section: Image 4 Haptic Dialed Into Anterior Chamber and Removal Of mentioning
confidence: 99%